Analisa Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Minat Beli Ulang pada Persebaya Store (Jurnal Simki Economic, 2023)
This study was conducted to analyze the effect of product quality, price perception on repurchase intention at Persebaya Store. Persebaya Store is a retail unit that was established to be a supporter in building a new image of the Persebaya club. As a center for selling Persebaya official merchandise (Official Merchandise Store). The method used is simple random sampling using quantitative research with descriptive statistical approach, as many as 110 respondents. Researchers used the entire population of Persebaya Store customers. The technique used by the researcher is validity test, reliability test, and simple linear regression analysis with SPSS (Statistical Product and Service Solution) tools. The results in this study indicate that the variables of product quality and price perception together have a significant influence on repurchase interest at Persebaya Store.